COVID-19 and Alimentary Tract: Current Evidence and Recent Recommendations - Yousif, Walid Ibrahim (AL-Kindy College Medical Journal, 2021)
The pandemic of coronavirus disease 2019 (COVID-19), first reported in China, in December 2019 and since then the digestive tract involvement of COVID-19 has been progressively described. In this review, I summed recent studies, which have addressed the pathophysiology of COVID-19-induced gastrointestinal symptoms, their prevalence, and bowel pathological and radiological findings of infected patients. The effects of gut microbiota on SARS-CoV-2 and the challenges of nutritional therapy of the infected patients are depicted. Moreover, I provide a concise summary of the recommendations on the management of inflammatory bowel disease, colorectal cancer, and performing endoscopy in the COVID era. Finally, the COVID pancreatic relation was explored. Conclusions: digestive symptoms in COVID-19 patients can be the only manifestation and they may be correlated with worse clinical outcomes. The likelihood of fecal-oral transmission of COVID-19 has significant consequences and requires further research. A clear link may exist between the gut microbiome and COVID-19 progression and it may have a therapeutic and prognostic value. No evidence for an increased frequency of covid-19 cases in IBD and stopping immunosuppressive medications is not advised. Triage and risk assessment of patients with suspected or confirmed COVID-19 before endoscopy is essential; deferral of elective endoscopies should be considered.